Hybrid Channel Model for Low Terahertz Links in a Data Center - Johannes M. Eckhardt; Tobias Doeker; Thomas Kurner (IEEE Open Journal of the Communications Society, 2024)
The aim of channel models is the effective prediction of wireless channels in applicationspecific environments in order to successfully design wireless communication systems. For THz communications, deterministic ray-optical channel predictions are very common. This paper shows inherent limitations of ray-tracing based models due to the accuracy of three-dimensional models of the environment in the context of THz communications and presents a new hybrid channel model approach that combines ray-optical channel predictions with an analytic path gain model extracted from measurements. The model is applied for switchable, point-to-point, wireless inter-rack links at THz frequencies in a data center that make the data center network reconfigurable at runtime. The channel parameters derived by the novel hybrid approach show promising results compared with channel parameters extracted from conducted reference measurements with an overall path gain error below 5 dB for residual multipath components.